Новая модификация безмодельного подхода к анализу данных по ядерной магнитной релаксации в белках - Федотов, В.Д.; Киваева, Л.С. (Биополимеры и клетка, 1987)
Развивается формальный подход к анализу релаксации ядер ¹³С в белках. Внутримолекулярное движение протонированных углеродов описывается обобщенными микродинамическими параметрами: фактором анизотропии (мерой пространственной ограниченности) и распределением времен корреляции. Обсуждается связь формальных параметров с параметрами некоторых моделей движения. Розвинуто формальний підхід до аналізу релаксації ядер ¹³С у білках. Внутрішньомолекулярний рух протонованих вуглеводів описується узагальненими мікродинамічними параметрами: фактором анізотропії (мірою просторової обмеженості) і розподілом часів кореляції. Обговорюється зв’язок формальних параметрів з параметрами деяких моделей руху. A formal approach to the analysis of data on magnetic relaxation of ¹³C nuclei in proteins is developed. It is based on ideology which has been used by one of the authors to study internal motions in solid polymers. According to the approach the intramolecular motions in proteins are considered as anisotropic ones and are characterized by a spectrum of the correlation times. A set of the formal microdynamic parameters such as an anisotropy parameter (a measure of spatial motion restriction), the most probable correlation time, a parameter of the correlation time distribution width is introduced to describe these motions. The causes resulting in non-exponential correlation function of local motion are discussed as well as a relation between formal parameters and microdynamic characteristics for concrete models of the motion.